THE EFFECT OF SMALL GROUP DISCUSSION TOWARDS STUDENTS WRITING SKILL AT SMKN 1 BANGKINANG - Ningsih, Wirda; FNU, Masrul; Rianti, Wida (TELL - US JOURNAL, 2023)
The purpose of this study was to determine the significant effect of the use of the small group discussion learning model on the writing skills of the students of SMKN 1 Bangkinang Kota. This research method uses experimental quantitative research with a quasi-experimental research design. The sample in the study consisted of 2 classes, namely the experimental class and the control class, totaling 71 students. The data collection instrument used pretest and posttest tests. The data analysis technique used normality test, homogeneity test, and hypothesis testing (t test). The results showed that the writing skills of the students of SMKN 1 Bangkinang Kota using the conventional learning model was with an average value of 76.34. Writing skills using the small group discussion learning model is with an average value of 79.76. The results of the "t" test obtained tcount > ttable, namely 2,914 > 2,009 with a significant level of 0.05 or 5% which states Ha is accepted and H0 is rejected. This proves that the small group discussion learning model has a significant influence on the writing skills of the students of SMKN 1 Bangkinang Kota